UHPLC-QTOF-MS phytochemical profiling and in vitro biological properties of Rhamnus petiolaris (Rhamnaceae) - ŞENKARDEŞ, İSMAİL (ELSEVIER, 2019)
The genus Rhanmus has a great attention as source of bioactive compounds. So, this work aimed to investigate phytochemical profile and biological activity of water and methanolic extracts of different parts of Rhamnus petiolaris Boiss. & Balansa, namely twigs, leaves, mature and unmature fruits. The in vitro antioxidant activity, enzyme inhibitory properties, along with their polyphenol and anthraquinone profiles were determined by untargeted metabolomics. Results showed that methanolic and aqueous unmature fruit extracts were the most effective 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) scavenger (470.96 mg trolox equivalent (TE)/g and 394.96 mg TE/g, respectively). The aqueous unmature fruit extract displayed the most potent cupric and ferric reducing power and showed the highest total phenolic contents (TPC) (137.17 mg gallic acid equivalent (GAE)/g). The methanolic twig extract showed the highest enzymatic inhibitory property against of alpha-glucosidase, tyrosinase, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). On the basis of the correlation coefficients calculated separately for all experimental parameter pairs, flavonols and anthocyanins highly correlated with DPPH, whereas tyrosols correlated with BChE activity. Multivariate statistics following untargeted metabolomics allowed to describe the differences in polyphenols and anthraquinones, as affected by the extraction solvent used. Mature and unmature fruits were substantially comparable and were affected in a similar way by the extraction conditions, while different profiles were recorded for Rhamnus leaves and twigs. These findings indicate that the recovery efficiencies of specific subclasses of compounds (above all when considering flavonoids, phenolic acids and anthraquinones) as a function of the matrix and extraction chosen, significantly affect the phytochemical profile and biological activity of Rhamnus.
Keywords: alpha-glucosidase; Tyrosinase; Bioactive compounds; Metabolomics; Orthogonal projection to latent structures; ANTIOXIDANT ACTIVITY; ANTHRAQUINONE PROFILE; PHENOLIC-COMPOUNDS; BARK EXTRACTS; ALATERNUS; INTERMEDIA; VIVO